Cuba, Jamaica and Porto Rico - J. H. Colton and Co. (1856)
Diagram represents a detailed drawing of Cuba, Jamaica and Porto Rico (Puerto Rico).
Level 3 deterioration.
Special Collections Floor.
Keywords: Cartographic material; Cuba; Jamaica; Puerto Rico; Maps